Sustainable and biocompatible hybrid materials-based sulfated polysaccharides for biomedical applications: a review - Alfinaikh, Reem S; Alamry, Khalid A; Hussein, Mahmoud A (RSC advances, 2025)
Sustainable biomaterials that are both efficient and environmentally friendly are the subject of research and development efforts among scientists and academics from a variety of contemporary scientific disciplines. Due to their significant involvement in several physiological and pathological processes, sulfated polysaccharides (SPs) have garnered growing interest across various application domains, including biomedicine. Nevertheless, mechanical and thermal stability are issues for unmodified polysaccharide materials. Interactions between polymers, such as the mixing of biopolymers with synthetic or biopolymers through chemical interaction or grafting into the main chain structure of raw materials to enhance their therapeutic effects, are essential to meet the high standards of biomedical features. Another way to improve the mechanical and thermal properties is to graft appropriate fillers onto the polysaccharide backbone. The characteristics of polysaccharide bio-nanocomposites in comparison to more traditional polymers have attracted a lot of interest. With an emphasis on anti-inflammatory, anticancer, antiviral, immunoregulatory, and anticoagulant properties, this review delves into the most recent biological uses of sulfated polysaccharides. As well as thoroughly outlining the factors that impact the biological properties, such as the extraction process, molecular weight (Mw), the degree of sulfation, distribution/position, modification procedures, and the filler size, etc. , this review aims to: (1) provide a systematic and critical overview of the cutting-edge research on SPs and hybrid sulfated polysaccharide bio-nanocomposites; (2) identify the key factors, mechanisms, methods, and challenges impacting SPs bio-nanocomposites; (3) elucidate the current and potential biomedical applications, advantages, manufacturing challenges, and opportunities associated with SPs bio-nanocomposites; (4) offer insights into future research directions by suggesting improvements for bio-nanocomposites, including novel materials, and advanced processing techniques. The work provides a systematic and critical overview of the cutting-edge research on SPs and hybrid sulfated polysaccharide bio-nanocomposites and identifies the key factors, mechanisms, methods, and challenges impacting SPs bio-nanocomposites.